2020
DOI: 10.1089/g4h.2019.0036
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Balance Games Provide Little Muscular Challenge to Prevent Muscle Weakness in Healthy Older Adults

Abstract: Objective: Muscle weakness is an important risk factor for falls in older adults. Intensity and duration of muscle activity are important determinants of exercise effectiveness in combating muscle weakness. The aim of this paper was to assess the intensity and duration of muscle activity in Virtual Reality (VR) balance games. Materials and Methods: Thirty young and thirty healthy older adults played seven different VR balance games. Muscle activity of the Vastus Lateralis, Vastus Medialis, Soleus and Gluteus M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…The remaining two were off-the-shelf games: Adventure, Kinect Adventures (Ubisoft, Rennes, France) and Kinski, Kinect sports season 2 (Microsoft Studios, Redmond, WA, US). Adventure and Kinski were included in this study because they showed to be the games that previously had most induced muscle activity and weight shifts [22,24].…”
Section: Gamesmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining two were off-the-shelf games: Adventure, Kinect Adventures (Ubisoft, Rennes, France) and Kinski, Kinect sports season 2 (Microsoft Studios, Redmond, WA, US). Adventure and Kinski were included in this study because they showed to be the games that previously had most induced muscle activity and weight shifts [22,24].…”
Section: Gamesmentioning
confidence: 99%
“…Based on the recommendations for balance and strength training, obtained from the literature [2,6,18,27] and our previous work in training using exergames [22,24,25], several concepts to be addressed in exergames balance training applications were proposed. In Fig.…”
Section: Gamesmentioning
confidence: 99%
See 3 more Smart Citations